2019
DOI: 10.1016/j.celrep.2019.11.045
|View full text |Cite
|
Sign up to set email alerts
|

DIRAS3 (ARHI) Blocks RAS/MAPK Signaling by Binding Directly to RAS and Disrupting RAS Clusters

Abstract: SUMMARY Oncogenic RAS mutations drive cancers at many sites. Recent reports suggest that RAS dimerization, multimerization, and clustering correlate strongly with activation of RAS signaling. We have found that re-expression of DIRAS3, a RAS-related small GTPase tumor suppressor that is downregulated in multiple cancers, inhibits RAS/mitogen-activated protein kinase (MAPK) signaling by interacting directly with RAS-forming heteromers, disrupting RAS clustering, inhibiting Raf kinase activation, and inhibiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…Zhang et al [ 10 ] evaluated DIRAS3 expression in paired adjacent normal and cancerous tongue tissue samples from 20 patients with tongue squamous cell carcinoma and found that DIRAS3 expression was significantly downregulated in cancerous tongue tissues. The re-expression of DIRAS3 led to retarded cell growth, angiogenesis, migration and invasion in breast, ovarian and liver cancer [ 11 13 ]. However, whether DIRAS3 re-expression can suppress tumor growth in HNSCC has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 10 ] evaluated DIRAS3 expression in paired adjacent normal and cancerous tongue tissue samples from 20 patients with tongue squamous cell carcinoma and found that DIRAS3 expression was significantly downregulated in cancerous tongue tissues. The re-expression of DIRAS3 led to retarded cell growth, angiogenesis, migration and invasion in breast, ovarian and liver cancer [ 11 13 ]. However, whether DIRAS3 re-expression can suppress tumor growth in HNSCC has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This growth promotion might be accomplished through the imprinted gene networks as mentioned above, although PLAGL1 was first discovered with its proapoptotic and antiproliferative molecular properties [ 11 , 12 ] and regarded as a tumor suppressor gene [ 15 , 18 ]. Nevertheless, this hypothetical theorem for imprinted paternal expression of tumor suppressor genes towards growth may not be generally applicable to other tumor suppressor genes, given that Igf2r is a maternally expressed imprinted gene in mice and inhibits embryonic growth [ 45 ] and DIRAS3 is a paternally expressed imprinted gene in humans (and in pigs, submitted for publication by our group) and also hinders growth [ 46 , 47 , 48 ], and both counteract the effects of growth promoting Igf2 and RAS , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mediated by adaptor proteins SHC (Src homology 2 domain containing) and Grb2 (growth factor receptor-binding protein 2), RTK activates SOS, which acts to substitute guanosine diphosphate (GDP) by GTP at the membrane to activate Ras (Bandaru et al, 2019;Huang et al, 2019;Liao et al, 2018Liao et al, , 2020. Membrane-anchored Ras dimers or nanoclusters bind and activate Raf kinase (Nussinov et al, 2019b(Nussinov et al, , 2019c(Nussinov et al, , 2020Solman et al, 2015;Sutton et al, 2019;Zhou et al, 2018). In the absence of Ras, Raf is autoinhibited.…”
Section: Ras: An Overviewmentioning
confidence: 99%